Dynamic behavior of sylvatic yellow fever in Brazil (1954-2008) Comportamento dinâmico da febre amarela silvestre no Brasil (1954-2008) - Fernando Portela Câmara; Ana Luisa Bessa Bacellar Gomes; Luiz Max Fagundes de Carvalho; Luiz Gustavo Veloso Castello (Sociedade Brasileira de Medicina Tropical (SBMT), 2011)
INTRODUCTION: Sylvatic yellow fever (SYF) is enzootic in Brazil, causing periodic outbreaks in humans living near forest borders or in rural areas. In this study, the cycling patterns of this arbovirosis were analyzed. METHODS: Spectral Fourier analysis was used to capture the periodicity patterns of SYF in time series. RESULTS: SYF outbreaks have not increased in frequency, only in the number of cases. There are two dominant cycles in SYF outbreaks, a seven year cycle for the central-western region and a 14 year cycle for the northern region. Most of the variance was concentrated in the central-western region and dominated the entire endemic region. CONCLUSIONS: The seven year cycle is predominant in the endemic region of the disease due the greater contribution of variance in the central-western region; however, it was possible identify a 14 cycle that governs SYF outbreaks in the northern region. No periodicities were identified for the remaining geographical regions. INTRODUÇÃO: A febre amarela silvestre (FAS) é enzoótica no Brasil, causando surtos periódicos em humanos que vivem próximos às áreas florestais ou em áreas rurais. Neste estudo, foram analisados os padrões de periodicidade desta arbovirose. MÉTODOS: Utilizamos a análise espectral de Fourier para capturar os padrões de periodicidades da FAS em séries temporais. RESULTADOS: Os surtos de FAS aparentemente não aumentaram em frequência, mas em número de casos. Há dois ciclos dominantes na FAS, um de sete anos predominando na região centro-oeste, e um de 14 anos predominando na região norte. A maior parte da variância concentrou-se na região centro-oeste e dominava toda região endêmica. CONCLUSÕES: O ciclo de sete anos é predominante para a região endêmica da doença devido a maior contribuição da variância do centro-oeste. No entanto, foi possível identificar um ciclo de 14 que rege a FAS na região norte. Não foram detectadas periodicidades nas demais regiões geográficas.